Analysis of Adverse Pregnancy Outcomes of Pregnant Women with Syphilis and Maternal-Infant Serological Association in Changzhou, China, 2015–2019 - Chaorong Bian; Zhiqiang Qin; Jieying Zhang; Mengtao Sun; Manman Gu; Kejin Chen (Stem Cells International)
Background. Although the prevention of mother-to-child transmission of syphilis program in China has achieved national coverage for 7 years, controversy still exists regarding the treatment of syphilis and the serological significance of syphilis. Objective. To explore the occurrence and influencing factors of adverse pregnancy outcomes among pregnant women with syphilis in Changzhou from 2015-2019 and to further analyze the impact of syphilis serologic titers on perinatal outcomes and neonatal serologic outcomes. Methods. Syphilis-infected pregnant women reported in Changzhou City from 2015 to 2019 were selected as the study population (data were obtained from the “China Information System for Prevention of Mother-to-child Transmission of AIDS, Syphilis and Hepatitis B.” Demographic characteristics, laboratory tests, and medication were collected to describe adverse pregnancy outcomes and the distribution of non-pale leptospiral antibody titers during pregnancy. Multivariate logistic regression was used to analyze the factors influencing adverse pregnancy outcomes. We also compared differences in syphilis titers among mothers who received different interventions, differences in serologic outcomes of their children, and correlations between them. Results. For mothers with syphilis infection, we found no treatment during pregnancy (OR =1.70) and an initial titer greater than 1 : 8 (OR =2.28) to be risk factors. For treated pregnant women, increasing age (OR =1.08), lack of standardized treatment (OR =1.87), and initial titer greater than 1 : 8 (OR =1.69) were risk factors, while previous parity was a protective factor (OR =0.62). For untreated pregnant women, marital status (OR =2.40) and initial titers greater than 1 : 8 (OR =3.57) were risk factors. There were statistically significant differences (P<0.01) in serologic titer changes, time to antibody regression, and time to exclusion of syphilis infection in children of pregnant women with syphilis infection after receiving different interventions during pregnancy, but different time distributions of interventions had no effect on these three indicators. Conclusion. Pregnant women with syphilis should actively cooperate with their doctors in the standardized treatment of pregnancy, and doctors should also pay more attention to pregnant women with syphilis whose initial titers are greater than 1 : 8. High-quality prenatal care is a key component in interrupting mother-to-child transmission of syphilis and preventing various adverse pregnancy outcomes. The adaptation of standardized treatment protocols for pregnant women with syphilis in China is a strong proof of the progress of precision medicine.